Pengaruh Keadilan, Kepatuhan, Pemeriksaan, Sistem dan Diskriminasi Perpajakan Terhadap Wajib Pajak Mengenai Penggelapan Pajak - Yusufin, Heiqal Bagas; Rakhmayani, Alfita (Jurnal Edueco, 2024)
This research aims to analyze Tax Justice, Tax Compliance, Tax Audit, Tax System and Tax Discrimination against Tax Evasion. The population in this study are individual taxpayers registered at PT. Pelindo Regional 2 Tanjung Priok. The sample for this research is individual taxpayers registered at PT. Pelindo Regional 2 Tanjung Priok. This research used the Slovin method and obtained a sample of 100 people. Data collection was carried out using a questionnaire method distributed to respondents and processed using SPSS version 26. Based on the results of the analysis, it shows that tax justice, tax inspection and tax discrimination have no effect on tax evasion, while tax compliance and the tax system have an effect on tax evasion.